HPLC method for the simultaneous determination of four compounds in rat plasma after intravenous administration of Portulaca oleracea L. extract (Brazilian Journal of Pharmaceutical Sciences, 2012)
The objective of the present study was to develop a simple and selective HPLC method for the simultaneous determination of hesperidin (HP), caffeic acid (CA), ferulic acid (FA) and p-coumaric acid (p-CA) in rat plasma after intravenous administration of Portulaca oleracea L. extract (POE). With the hyperoside as the internal standard, the sample pretreatment procedure involved simple single-step extraction with methanol of 0.2 mL plasma. The mobile phase consisted of methanol-acetonitrile-tetrahydrofuran-0.5% glacial acetic acid (5:3:18:74, v/v/v/v). The calibration curves were linear over the range of 0.1-25 µg mL-1, 0.1-25 µg mL-1, 0.1-25 µg mL-1and 0.015-3 µg mL-1 for HP, CA, FA and p-CA, respectively. The method developed was suitable for the pharmacokinetic study of HP, CA, FA and p-CA in rats after intravenous administration of POE.